Pengaruh Tokoh Agama, Komunikasi Persuasif, Motivasi dan Kognisi Masyarakat terhadap Pelaksanaan Protokol Kesehatan - Teddy Dyatmika (IAI Darussalam, 2021)
This study aims to determine how much influence the variables of religious leaders, persuasive communication, motivation, and community cognition together have on the implementation of the protocol in Tegal City. The research method used is quantitative with the number of samples used as many as 100 respondents. The sampling technique used a proportional stratified sampling technique with a standard error of 10%. The theory used in this research is the Elaboration Likelihood Model theory by Petty and Cacioppo. The analysis technique used is multiple linear regression. The results of this study indicate that there is a significant influence of the four independent variables of religious leaders, persuasive communication, motivation, and community cognition together on the implementation of the protocol. The magnitude of the resulting effect is 0.73 or 73%. There is still 27% of the effect resulting from other variables related to the implementation of health protocols in Tegal City.